Carbamazepine Toxicity with Generic Substitution - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Two 6-year-old children with carbamazepine (CBZ) toxicity, reported from the University of Miami School of Medicine, were found to have 22% and 41% increases in serum CBZ levels after substitution of Tegretol with the generic brand, Epitol, because of insurance company policies.